Research on Load Balancing in C-RAN with Femtocells - Zhanjun Liu; Xia Peng; Yujing He; Qichao Ma (Universitas Ahmad Dahlan, 2016)
The traditional load balancing optimization scheme cannot guarantee the user’s QoS in the C-RAN wireless communication networks when all the neighboring macrocells are under the situation of overload. In order to resolve this problem, we implement the femtocell to the macrocell network, which considers the advantages of femtocell, i.e., small coverage, low cost and better signal quality. Therefore, in this paper, the joint load balancing mechanism is proposed to achieve the joint optimization of femtocell and macrocell network by allowing the users of overloaded macrocell to handover to the femtocell. Finally, the simulation results show that the proposed mechanism greatly improves the user satisfaction as well as the resource utilization rate of the femtocell network while decreases the blocking rate and dropping rate.